Densification Mechanisms Made During Creep Techniques Applied to the Hot Isostatic Pressing - Radomir, Irinel; Geamăn, Virgil; Stoicănescu, Maria (Elsevier BV, 2012)
Hot isostatic compression involves the simultaneous application of pressure and elevated temperature to materials. The pressure applied, usually by a gas, is isostatic because it's developed in a suitable pressurized vessel by a fluid. Therefore in principle no alteration in component geometry occurs. Under these conditions of heat and pressure, internal pores or defects within a solid body or a powder compact collapse and weld up. Encapsulated powder and sintered components densify easily and faster than due to sintering alone. Therefore HIP is today used for a lot of applications, like upgrading castings (removing shrinkage pores in interdendritic space), densifying pre-sintered components, consolidation of powders and interfacial bonding. The paper presents some technical data regarding to densifying mechanism made by different creep techniques.
Keywords: HIPcompression mechanismfull densitycreep